Needs, Rights and Systems: Increasing Canadian Intimate Bystander Reporting on Radicalizing to Violence - Thompson, Sara K. (Terrorism and political violence, 2024)
The first people to suspect or know about someone involved in acts of violent extremism will often be those closest to them: their friends, family and community insiders. They are ideally placed to play particular roles: (a) to notice any changes or early warning signs that someone is considering violent action to harm others, and (b) to influence and facilitate vulnerable individuals to move away from violent extremist involvements. The willingness of those close to potential or suspected violent actors to come forward and share their knowledge and concerns with authorities is thus a critical element in efforts to prevent violent extremist action. This Canadian study replicates the focus and methodology of three previous Community Reporting Thresholds studies with an increased scope and sample size. Our findings highlight the ways in which Canadian community respondents framed their understanding of and engagement with reporting as intimate bystanders on someone close radicalising to violence in relation to three main domains: needs-based, rights-based and systems-based. This paper will explore what we have learned from data across three Canadian cities with a particular emphasis on how the domains of needs, rights and systems are conceptualized and enacted by Canadian respondents.